In plain sight: the LGBT community in the Kansas Flint Hills - Haddock, Brandon Harley (Kansas State University, 2016)
This research examines the intersections of sexuality and gender identity and how differing socio-cultural networks are important to how we can begin to address multiple issues affecting rural America. The overarching question of the research was: How do sexuality and gender identity minorities living in rural areas experience or perceive where they live and the community networks that they navigate? Subtopics included the factors that contribute to an LGBT individual living in the Flint Hills, whether individual sexual and gender identities and perception affect concepts of location and community, and how one’s sexuality or gender identity affects the lived experience in a rural region. A multi-disciplinary approach based on Geography and LGBT Studies, using interviews and surveys of distinctive rural populations in the Flint Hills of Kansas, was applied. Five focus groups and 31 individual interviews yielded information about LGBT community concerns in the Flint Hills. A broader region was represented through an electronic survey which accessed a large population anonymously through a variety of social networking sites. The survey yielded 119 complete responses. Discrimination was a concern and sense of community was important. Many individuals acknowledged that they had a system of navigation of rural environments: where to go, to whom to speak openly, how to blend in to the larger population. Despite fears that were expressed, there was a sense of resilience among participants related to living in a relatively rural region. A sense of queer community and an acknowledgement of a rural community were important. Community connections are a major factor contributing to the individual’s lived experience and perception of the Flint Hills. For most of the participants, identity as a rural LGBT person or as part of the (relatively) rural queer community is important. There is a strong affinity to what individuals view as rural, and they view rural as being different from urban landscapes and communities.
Keywords: Geography; CommunityRural queer